AN EXPERIMENTAL DIALOGUE WITH POSTMODERNISM: (RE) READINGSAMUEL BECKETT’S KRAPP’S LAST TAPE - John , Reenu S (International Journal of Psychosocial Rehabilitation, 2020)
The proposed study is placed on the interstices of the postmodern literary condition and Gender studies. This interstice is crucial in the current scenario where on the one side we witness more global mobility and visibility of women and yet there prevails certain ‘spirals of silence’ that jettison women. The attempted close analysis of literary work may be seen as take-off point as to how representation in the broad social sense feeds into this scenario. The attempted work is rather a dialogue between two works with different subject positions. The paper attempts to try and possibly problematize the interface that is usually discussed within postmodernist representations and the concerns of Gender Studies. This is vital because, in a big way discussions of the same tend to conflate gender, and in doing so bypass the women’s question, not just in literary texts but generally in ‘social narratives’ The objective here is to create a space, especially in the social reality that is India, where the issue of the Woman’s voice can be recovered for reasoned debate and reflection.